Os acordos de leniência e a experiência do Ministério Público do Estado do Paraná - Oliveira , Aysha Sella Claro de (2021)
Corruption as an endemic practice, institutionalized and of significant global concern, knows no borders. The constitutional role given to the Public Prosecutor's Office, added to the attributions that are incumbent upon it, contributes and brings the Institution, above all, to the Sustainable Development Goals of the 2030 agenda. From the inductive and empirical methods, the agreements signed by the Public Ministry of the State of Paraná were analyzed. The conclusion shows that the adjustments have been fully complied with or are in the process of being complied with, without any news of non-compliance with the agreed obligations. In addition, the full investigation that gave rise to the signing of the agreements detected the participation of a public and/or political agent in the illegal activities, while most of the illegalities concern the procurement of goods and services by the Public Administration through public bids. The agreements promoted an effective increase in investigations, which even implied the filing of complaints for criminal accountability of other agents involved in the illicit objects of the pacts. In addition, all leniency agreements contemplate full compensation for the damage suffered by the Public Administration, when applicable, and only two were not agreed to co-existing with awarded collaboration agreements entered with the partners, administrators, agents and/or directors of lenient legal entities. Finally, combating corruption in a preventive and reactive manner, expanding cooperation between State institutions, powers and bodies, expanding transparency and good public management techniques, improving legislation and using consensus in the sanctioning law, are measures that are inescapable to sedimentation of a new and better path towards the realization of fundamental human rights and guarantees and the effective protection of public assets and administrative probity, guaranteed in the Federal Constitution.